2015
DOI: 10.1021/acsami.5b05627
|View full text |Cite
|
Sign up to set email alerts
|

Probing the Surface Hydration of Nonfouling Zwitterionic and PEG Materials in Contact with Proteins

Abstract: Zwitterionic polymers and poly(ethylene glycol) (PEG) have been reported as promising nonfouling materials, and strong surface hydration has been proposed as a significant contributor to the nonfouling mechanism. Better understanding of the similarity and difference between these two types of materials in terms of hydration and protein interaction will benefit the design of new and effective nonfouling materials. In this study, sum frequency generation (SFG) vibrational spectroscopy was applied for in situ and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
244
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 241 publications
(263 citation statements)
references
References 55 publications
9
244
1
Order By: Relevance
“…[27][28][29] In the past SFG spectroscopy has frequently been used to investigate the hydration of PEGylated surfaces in presence or absence of proteins in the subphase. [30][31][32][33][34][35][36][37] Moreover, there are several in situ studies probing the water structure or protein backbone in the amide I region after adsorption on hydrophobic or hydrophilic surfaces. 28,[38][39][40][41][42][43][44] Understanding the interaction of proteins with PEGylated surfaces plays an important role e.g.…”
Section: Introductionmentioning
confidence: 99%
“…[27][28][29] In the past SFG spectroscopy has frequently been used to investigate the hydration of PEGylated surfaces in presence or absence of proteins in the subphase. [30][31][32][33][34][35][36][37] Moreover, there are several in situ studies probing the water structure or protein backbone in the amide I region after adsorption on hydrophobic or hydrophilic surfaces. 28,[38][39][40][41][42][43][44] Understanding the interaction of proteins with PEGylated surfaces plays an important role e.g.…”
Section: Introductionmentioning
confidence: 99%
“…The zwitterionic polymers show water sorption ( v W ) similar to XLPEGDA, indicating that the zwitterionic polymers are comparable to the PEG‐containing materials in terms of hydrophilicity. This result also corroborates with the observation that the better antifouling properties in zwitterionic polymers than nonion‐containing PEG‐based materials are due to the amphiphilic nature in PEG that has nonspecific hydrophobic interactions with foulants, instead of more water layers bound by the zwitterionic polymers.…”
Section: Resultsmentioning
confidence: 97%
“…Increasing the zwitterionic monomer content has two effects on the polymers: higher content of ionic groups that are expected to have higher affinity with water, and lower crosslinking density that is expected to increase the water sorption . To decouple these two effects, the water sorption in the zwitterionic polymers is compared with that of XLPEGDA prepared from prepolymer solutions containing PEGDA and H 2 O, as shown in Figure (b).…”
Section: Resultsmentioning
confidence: 99%
“…The previous studies demonstrated that the negatively charged groups (SO 3 - and COO − ) in heparin reduced absorption of albumin (isoelectric point; PI = 4.8) and fibrinogen (PI = 5.5) proteins by electrostatic repulsion effect, and the non- fouling degree against protein absorption was dependent on the surface heparin density [44]. In addition, the hydrophilic polymer-bound surface can also serve as a physical barrier against protein/platelet absorption through hydrogen bond-induced surface hydration [45, 46]. …”
Section: Resultsmentioning
confidence: 99%